L-moment-based frequency analysis of high-flow at Sungai Langat, Kajang, Selangor, Malaysia - Firdaus Mohamad Hamzah,; Siti Hawa Mohd Yusoff,; Othman Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Annual maximum daily streamflow data were used to examine flood frequency for Sungai Langat in Kajang, Selangor, Malaysia. The objectives of this study were to identify the best fit probability distribution to the streamflow data and estimate the return period of the extreme flood events. The L-moment method was implemented to estimate the parameter of probability, by using distributions namely Gamma, LN3, GEV, PE3, GLO and Kappa. It was found that Kappa distribution was the best fitting distribution to the data after being tested using the goodness-of-fit tests. The Kappa distribution gave the most appropriate to the annual maximum series data of Sungai Langat, Kajang, Selangor. The return values were calculated using Kappa distribution model. The return period of 2 years gave the return value of 49.09 m3/s, while return period of 100 years gave the return value of 390.54 m3/s.